The global business game : a strategic management and international business simulation : player's manual - Wolfe, Joseph A. (Joseph Allen), 1935- (Cincinnati, OH : South-Western College, 1999)
This book is about: The global household Audio and Video equipment industry; Company history and background; Organizing company operations; Marketing and marketing logistics; ...
Keywords: Management; Simulation methods; Management -- Study and teaching -- Simulation methods